HISTOMORPHOMETRY OF GRANULOCYTES BALI CATTLE SEEDLINGS IN NUSA PENIDA - Mami, Oktavyan Loys; Suwiti, Ni Ketut; Setiasih, Luh Eka (Buletin Veteriner Udayana, 2021)
The aim of this research were to find out the granulocyte histomorphometry of bali cattle in Nusa Penida. The sample are taken from 50 female blood bali cattle. Blood collection is carried out through the jugular vein using venoject. Making blood smears using the slide method was done at the sampling site, followed by fixation and staining of Giemsa. The measurement of granulocyte diameter was carried out using the Axio Imager Zeiss 2 microscope and ZEN 2012. software The data obtained were analyzed by descriptive statistics. The mean of granulocyte histomorphometry in Nusa Penida was 9.1±1,4 ?m neutrophils, 8.9±1,6 ?m eosinophils, and 8.9 ±1,7?m basophils with a range of 6-11 ?m in neutrophils, 5-13 ?m in eosinophils, and 5-11 ?m in basophils.